Minoxidil and its use in hair disorders: a review - Suchonwanit P; Thammarucha S; Leerunyakul K (Dove Medical Press, 2019)
Poonkiat Suchonwanit, Sasima Thammarucha, Kanchana LeerunyakulDivision of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandAbstract: Minoxidil was first introduced as an antihypertensive medication and the discovery of its common adverse event, hypertrichosis, led to the development of a topical formulation for promoting hair growth. To date, topical minoxidil is the mainstay treatment for androgenetic alopecia and is used as an off-label treatment for other hair loss conditions. Despite its widespread application, the exact mechanism of action of minoxidil is still not fully understood. In this article, we aim to review and update current information on the pharmacology, mechanism of action, clinical efficacy, and adverse events of topical minoxidil.Keywords: alopecia, beard, eyebrow, hair loss, hair shaft disorders, treatment